Preparation of Briquettes on the Basis of Sub-Standard Coal of Kazakhstan Fields - Tulepov, Marat; Sassykova, Larissa; Kerimkulova, Almagul; Tureshova, Gulmira; Abdrakova, Fedosya; Zhapekova, Anar; Sultanova, Zukhra; Spanova, Galiya; Tolep, Dana; Gabdrashova, Sholpan; Baiseitov, Dauren (Видавництво Львівської політехніки, 2022)
Розроблена технологія брикетування некондиційного вугілля казахстанських родовищ для отримання високоякісного брикетного палива. Вибрана модифікуюча добавка у вигляді нафтових залишків, яка дає можливість отримати зв‘язуюче для брикетування бурого вугілля. Матеріалом для приготування брикетів є вугільний дрібняк, одержаний з сухого вугілля, що погано спікається, і яке не може використовуватись для безпосереднього спалювання в печі. Визначено оптимальні параметри для отримання високоякісних паливних брикетів. Введення модифікуючої добавки до нафтових залишків дає можливість отримати зв‘язуюче для брикетування. Дослідження фізичних параметрів брикетів та дані SEM показали, що товщина адсорбційного шару вугілля та зчеплення зв‘язуючого в тонких шарах відіграють важливу роль у формуванні структури та міцності брикету. Зроблено припущення, що за оптимальної товщини шару плівки має місце максимальний прояв капілярних сил і збільшення адгезивної взаємодії між частинками і зв‘язуючим. Органічний компонент вугільного дрібняку – це суміш різних рентгеноаморфних компонентів, наявність і кількість яких змінюється в ряді метаморфізму. Показана можливість та перспективи використання місцевої сировини для розроблення високоякісного брикетованого буровугільного палива.

A technology of briquetting of sub-standard coal of Kazakhstan fields to obtain high-quality briquetting fuel has been developed. A modifying additive in the form of oil residues has been selected, that make it possible to obtain a binder composition for brown coal briquetting. The material for the preparation of coal briquettes is coal fines from dry, poorly sintered coals, which cannot be used for direct combustion in the furnace. The optimal parameters for obtaining high-quality fuel briquettes have been determined. The introduction of a modifying additive into the oil residues makes it possible to obtain a binder composition for briquetting brown coal. Studies of the physical parameters of briquettes and the data of SEM showed that the thickness of the adsorption layer of coal and the cohesion of the binder in thin layers play an important role in the formation of the structure and strength of the briquette. It was assumed that at the optimum thickness of the film layer, the maximum manifestation of capillary forces and an increase in the adhesive interaction between the particles and the binder take place. The organic component of the coal fines is a mixture of various X-ray amorphous components, the presence and number of which vary in a series of metamorphism. The results of the performed studies show the possibility and prospects of using local raw materials for the development of high-quality briquetted brown coal fuel.
Приготування брикетів на основі некондиційного вугілля казахстанських родовищ
Keywords: вугілля; брикетування; зв‘язуюче; гудрон; теплотворна здатність; енергетичні показники; родовище; coal; briquetting; binder; tar; calorific value; energy performance; deposit